A bibliometric analysis of endoplasmic reticulum stress and atherosclerosis - Huang, Xinyu; Jiang, Feng; Ma, Yongbo; Zhu, Kunpeng; Wang, Zhenyuan; Hua, Zhen; Yu, Jie; Zhang, Lei (Frontiers in Physiology, 2024)
The mechanisms underlying the occurrence and development of atherosclerosis (AS) are diverse, among which endoplasmic reticulum stress (ERS) is an important mechanism that should not be overlooked. However, up to now, there has been no bibliometric study on the relationship between ERS and AS. To understand the research progress in ERS and AS, this paper conducted a statistical analysis of publications in this field using bibliometrics. A total of 1035 records were retrieved from the Web of Science Core Collection. CiteSpace, VOSviewer, and the R package "bibliometric" were used to analyze the spatiotemporal distribution, countries, authors, institutions, journals, references, and keywords of the literature, and to present the basic information of this field through visualized maps, as well as determine the collaboration relationships among researchers in this field. This field has gradually developed and stabilized over the past 20 years. The current research hotspots in this field mainly include the relationship between ERS and AS-related cells, the mechanisms by which ERS promotes AS, related diseases, and associated cytokines, etc. Vascular calcification, endothelial dysfunction, NLRP3 inflammasome, and heart failure represent the frontier research in this field and are becoming new research hotspots. It is hoped that this study will provide new insights for research and clinical work in the field of ERS and AS.